Pathways to higher education for vocationally qualified students. The case of Norway - Johannes K. Schmees; Eli Smeplass; Asgeir Skålholt; Elisabeth Hovdhaugen; Christian Imdorf (Taylor & Francis Group, 2024)
This article investigates six pathways through which students possessing initial vocational qualifications can enter higher education in Norway. In Norway, vocational education and training (VET) tracks in upper secondary education are popular nationwide with the youth population, catering to almost half of every youth cohort. However, despite explicit goals to promote social mobility through education, there is evident reproduction of social inequalities in attraction to and completion of higher education programmes. This issue is of paramount importance for the welfare state context, given that students in VET tracks typically come from lower socioeconomic backgrounds compared to their peers in general education pathways. Therefore, prohibited permeability between VET and higher education undermines universal access to higher education. This study is designed in a threefold manner: First, the connection between VET and socioeconomic background is investigated, leading to the conclusion that underprivileged youth are overly represented in VET pathways. Secondly, we explore alternative routes to higher education available to vocationally qualified students in Norway; and thirdly, we present available data on to what extend these pathways facilitate access to higher education. We conclude that limited permeability is a social problem and discuss possible means to address the issue.